Variability of Radio AGN in the CHILES Field - Peters, Charee (Proceedings of the Wisconsin Space Conference, 2018)
It is clear from previous and ongoing surveys that there are many sources that change in brightness over time. There is a wide range of extragalactic phenomena that create events with time-varying brightness. Variable sources have regular changes in brightness, such as the steady accretion of matter onto a super massive black hole at the center of a galaxy, known as active galactic nuclei (AGN). Despite strongly emitting in radio wavelengths, the radio sky is nearly completely unexplored in terms of these variable events. Most radio surveys on AGN variability have not been deep enough, include a small sample, and only have a few observations to understand how AGN are changing on timescales between weeks and months. Improving our understanding of the fundamental nature these sources requires a deep radio continuum survey with extension data to observe changes happening on timescales longer than days and less than years. The combination of the COSMOS HI Large Extragalactic Survey (CHILES) and 14 hours of extension observations, I will begin to answer: what is the variability of radio AGN and can it be used to predict and classify future events?